QT and QTc in Male Patients with Psychotic Disorders Treated with Atypical Neuroleptics - Mario Miniati; Marly Simoncini; Federica Vanelli; Caterina Franceschini; Gabriele Massimetti; Claudia Carmassi; Liliana Dell’Osso (The Scientific World Journal)
Objective. We explored the potential association between antipsychotics and QT/QTc duration changes in hospitalized male patients with psychotic disorders. Methods. The chart review was conducted on 184 male patients hospitalized between 2013 and 2015 at the Psychiatric Clinic of Pisa, Italy. Patients who were treated with one atypical antipsychotic at the time of the ECG recording were 109/184 (59.2%). QT/QTc were compared considering the atypical antipsychotic received. Results. 96.3% (n = 105/109) of the sample showed QTc values ≤ 430 ms; 4 patients (3.7%) had QTc values between 430 and 450 msec (2 with paliperidone, 1 with risperidone, and 1 with olanzapine). The mean QT duration of the overall sample was 368.0 ± 28.0 and the mean QTc 400.1 ± 17.8. QTc values did not reveal statistically significant differences. QT values were significantly different (chi-square = 17.3; df = 5; p = .004). Statistically significant differences between aripiprazole and paliperidone (349.0 ± 28.3 versus 390.5 ± 29.8; p = .002) and between clozapine and paliperidone (361.1 ± 22.43 versus 390.5 ± 29.8; p = .033) were found. Conclusions. Aripiprazole was the least interfering neuroleptic with QT/QTc. Paliperidone was the atypical neuroleptic with the most relevant difference with aripiprazole, but only on QT.